An extended macro-finance model with financial factors - Hans Dewachter; Leonardo Iania (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper extends the benchmark Macro-Finance model by introducing, next to the standard macroeconomic factors, additional liquidity-related and return forecasting factors. Liquidity factors are obtained from a decomposition of the TED spread while the return-forecasting (risk premium) factor is extracted by imposing a single factor structure on the one-period expected excess holding returns. The model is estimated on US data using MCMC techniques. Two findings stand out. First, the model outperforms significantly most structural and non-structural Macro-Finance yield curve models in terms of cross-sectional fit of the yield curve. Second, we find that financial shocks, either in the form of liquidity or risk premium shocks, have a statistically and economically significant impact on the yield curve. The impact of financial shocks extends throughout the yield curve but is most pronounced at the high and intermediate frequencies.
Keywords: C11; E44; G12; 330; yield curve; affine models; macroeconomics and financial factors; Bayesian estimation; Zinsstruktur; Ökonometrisches Makromodell; Gesamtwirtschaftliche Liquidität; Risikoprämie; Kapitalertrag; Theorie; USA